2017
DOI: 10.1063/1.4985380
|View full text |Cite
|
Sign up to set email alerts
|

Electrostatic/magnetic ion acceleration through a slowly diverging magnetic nozzle between a ring anode and an on-axis hollow cathode

Abstract: Ion acceleration through a slowly diverging magnetic nozzle between a ring anode and a hollow cathode set on the axis of symmetry has been realized. Xenon was supplied as the propellant gas from an annular slit along the inner surface of the ring anode so that it was ionized near the anode, and the applied electric potential was efficiently transformed to an ion kinetic energy. As an electrostatic thruster, within the examined operation conditions, the thrust, F, almost scaled with the propellant mass flow rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 18 publications
0
18
0
Order By: Relevance
“…They recognised that a lack of available solar power has historically prevented AF-MPDTs from being considered for spaceflight operation, in spite of the fact that they had shown promise for near-to mid-term propulsion requirements [8] [56]. They decided to implement a hybrid approach, whereby a thruster contains elements of both applied-field electromagnetic thrusters, and of gridless electrostatic thrusters [71]. The studies thus far have indicated that there is a wealth of new research to conduct on this hybrid approach [71]- [76].…”
Section: Resolving the Conundrum: Combining Forcesmentioning
confidence: 99%
See 4 more Smart Citations
“…They recognised that a lack of available solar power has historically prevented AF-MPDTs from being considered for spaceflight operation, in spite of the fact that they had shown promise for near-to mid-term propulsion requirements [8] [56]. They decided to implement a hybrid approach, whereby a thruster contains elements of both applied-field electromagnetic thrusters, and of gridless electrostatic thrusters [71]. The studies thus far have indicated that there is a wealth of new research to conduct on this hybrid approach [71]- [76].…”
Section: Resolving the Conundrum: Combining Forcesmentioning
confidence: 99%
“…They decided to implement a hybrid approach, whereby a thruster contains elements of both applied-field electromagnetic thrusters, and of gridless electrostatic thrusters [71]. The studies thus far have indicated that there is a wealth of new research to conduct on this hybrid approach [71]- [76]. Some key findings have been increased operational efficiency at low power over an AF-MPDT, increased thrust density over HETs, and results of efficiency improvement with different magnetic field topologies.…”
Section: Resolving the Conundrum: Combining Forcesmentioning
confidence: 99%
See 3 more Smart Citations